النظري التصوري والقيم والمبادئ للأخلاق الكريمة في منظور القرآن الكريم - Qasim, Amrah Muhammad (Shaut al Arabiyyah, 2016)
This writing is entitled “....................” The writing discusses the basic principles of Al-Quran and ethics, as well as its application to human interaction with God (ubudiyah), human itself, and environment. In the Al-Quran is mentioned, that there is a balance of God’s creation, such as universe, environment, and social life. Based on this balance, God creates rules through Al-Quran, particularly ethics value and laws in order to keep the balance and to avoid disasters. Therefore, Islamic teaching could be realized in the human life, if the basic concept of Al-Quran that contains “akhlaqul karimah” (Islamic ethics) is implemented.